Membumikan Pluralisme Di Indonesia: Manajemen Konflik Dalam Masyarakat Multikultural - Khoirul Fatih, Moh. (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2018)
Indonesia is a multicultural country with people living in diverse cultures, ethnics, and languages. Reality of plurality should not be ignored from our lives. Indonesia needs a conflict management in the life of a pluralistic society. For Facing this with all, we must apply a pluralism in plurality of religions and cultures.Therefore importance of dialogue as a means for mutual understanding between cultures and religions. In this article, idea of pluralism can be realized in a dialogue that is based on the guidelines of the nation contained in the values of Pancasila. While manage a conflict on dialogue, we also can increase development in our country with include discussion in various sector such as social, economy, and prosperity.